Effect of the calcium phosphorus ratio on bone characteristics, percent of ashes and skeletal integrity of broilers - Uculmana M., Cristian (2018)
The aim of this study was to determine the effect of the ratio calcium (Ca) and available phosphorus (AP) on the bone morphometry and mineralization, and skeletal integrity of broilers. Sixty one day-old Cobb 500 chicks were distributed in 12 experimental units and assigned, for 21 days, to one of the following treatments: T1, low Ca:Pd (1.13); T2, medium Ca:Pd (1.55); T3, adequate Ca:Pd (1.98). All diets contained 3072 Kcal ME/kg and 20.50% crude protein. Feeds, in meal form, and water were offered ad libitum. At day 21 of age all animals were slaughtered to extract the femur, tibia and metatarsus. Variables that included bone morphometry (weight, length, width, volume and density), skeletal integrity (ability to walk and lesions in the femoral head) were measured and the content of ash in the tibia was determined. The data was analyzed under a Complete Randomized Design using the ANOVA procedure and Duncan Test for comparison of the means. The results showed that the content of ash in tibia was significantly affected (p<0.01) by the dietary Ca:Pd ratio. Compared with the 1.98 and 1.55 Ca:Pd ratios, the 1.13 Ca:Pd ratio affected (p<0.03) the capacity to walk and the density of the tibia (p<0.05). In conclusion, the ash content in tibia is sensitive to changes in the Ca:Pd ratios while skeletal integrity indicators are only affected when the Ca:Pd ratio was lower than1.55.